Adaptation and potential culture of wild Amphipods and Mysids as potential live feed in aquaculture: a review - Suhaimi, Hidayu; Abdul Rahman, Muhammad Irfan; Ashaari, Aisyah; Ikhwanuddin, Mhd; Wan Rasdi, Nadiah (PeerJ, 2024)
Live foods such as phytoplankton and zooplankton are essential food sources in aquaculture. Due to their small size, they are suitable for newly hatched larvae. Artemia and rotifer are commonly used live feeds in aquaculture; each feed has a limited dietary value, which is unsuitable for all cultured species. Whereas, copepod and cladocerans species exhibit favorable characteristics that make them viable candidates as sources of essential nutrients for hatchery operations. Due to their jerking movements, it stimulates the feeding response of fish larvae, and their various sizes make them suitable for any fish and crustacean. Even though Artemia is the best live feed due to its proficient nutritional quality, the cost is very expensive, which is about half of the production cost. A recent study suggests the use of amphipods and mysids as alternative live feeds in aquaculture. High nutritional value is present in amphipods and mysids, especially proteins, lipids, and essential fatty acids that are required by fish larvae during early development. Amphipods and mysids are considered abundant in the aquatic ecosystem and have been used by researchers in water toxicity studies. However, the culture of amphipods and mysids has been poorly studied. There is only a small-scale culture under laboratory conditions for scientific research that has been performed. Thus, further research is required to find a way to improve the mass culture of amphipods and mysids that can benefit the aquaculture industry. This review article is intended to provide the available information on amphipods and mysids, including reproductive biology, culture method, nutritional value, feed enhancement, and the importance of them as potential live feed in aquaculture. This article is useful as a guideline for researchers, hatchery operators, and farmers.
Keywords: Aquaculture live feed; Amphipods; Mysids; Adaptation; Wild live feed; Culture; Nutrition manipulation; Protein; Lipid; Fatty acids